GE_GERICHTE C/13432/2017 vom 12. Februar 2018 - GE Cour de justice (2018)
PROCÉDURE DE CONCILIATION ; DEMANDE ADRESSÉE À L'AUTORITÉ ; FORME ET CONTENU ; FORMALISME EXCESSIF | CPC.202.al2; CPC.132.al1; Cst.29.al1